The choice of mechanisms and technologies to build online trust in e-commerce website and the influence of personal characteristics - Flora Membuas (2011)
Aim of this study was to investigate the preference of mechanism and technologies to build online trust among consumer towards e-commerce website. Mechanisms and technologies that being studied were secure communication channel mechanism, interaction with past consumers, clear policy, website design, third party services, company information, and products or services information. The selection of mechanisms and technologies are influenced by the gender, e-commerce experience, Internet experience and personality being study to investigate influence of these factors. This study adopted quantitative approach, use questionnaire as instrument and samples were 226 postgraduate from one of the public institutions of higher education (IPTA) in Malaysia. To determine the effect of the selection mechanism and the existence of such technology, comparison of mean values using t test and ANOVA test were performed. It was found that only Internet experience affects online trust towards e-commerce website while gender, type of personality and e-commerce experience do not influence online trust. For e-retailing and e-service website, clear policy is the most important mechanism to build online trust while for e-banking website, third party services has been selected. E-commerce website in future is recommended to have these seven trust triggers to attract consumers to engage with e- commerce transactions. Overall, secure communication channel is the most important technology for e-commerce website to build online trust among consumers.